Changes in surface morphology of helium-induced tungsten nanostructure during high-temperature annealing. (January 2020) - Wong, Chun-Shang; Whaley, Josh A.; Wada, Takuro; Harayama, Sakumi; Oya, Yasuhisa; Kolasinski, Robert D.
Highlights: He-induced tungsten nanostructure can recrystallize at low temperatures ( < 1300 K) Spectroscopic ellipsometry can track surface recovery of tungsten in-situ Thermal desorption spectroscopy reveals helium release peaks at 373 K and 1123 K Changing surface morphology may affect TDS of helium-exposed tungsten. Abstract: When exposed to high-flux helium plasmas, tungsten is known to develop a surface nanostructure called tungsten fuzz. Although there exists a consensus for the general mechanisms that lead to this nanostructure, a number of questions regarding its formation have yet to be addressed. One common approach to investigate helium-tungsten interactions is thermal desorption spectroscopy (TDS), as TDS can offer insight into the trapping of helium in tungsten that ultimate drives the nanostructure growth. However, during TDS, the surface morphology of the tungsten nanostructure can change dramatically at temperatures substantially lower than those required to fully desorb the trapped helium. For a comprehensive interpretation of TDS spectra, the helium release from trapping sites should be disentangled from complications that may arise from the changing surface morphology. In this work, we characterize the effects of high-temperature annealing on the surface morphology of tungsten nanostructure during TDS. Six ITER-grade W samples were exposed to helium plasma under identical conditions (a He ion fluence Φ i = 8.6 × 10 24 m − 2, ion energy of 90 eV, and sample temperature of 1123 K) to generate similar surface nanostructures on each sample. Samples were then annealed at various temperatures for different durations to determine the impact of annealing temperature and duration on the surface nanostructure. During annealing, TDS spectra of the He release rate were obtained using a quadrupole mass spectrometer, yielding He release peaks near 373 K and 1123 K. Changes to the surface morphology were observed on samples annealed at temperatures as low as 1173 K, using a combination of spectroscopic ellipsometry and helium ion microscopy with focused ion beam profiling.